The kinetic analysis of γ-aminobutyric acid (GABA) production in buckwheat after high hydrostatic pressure - Ishikawa, Daitaro; Onozawa, Genki; Tanji, Hiroyuki; Fujii, Tomoyuki (Food Science and Technology Research, 2024)
We aimed to investigate the effect of high hydrostatic pressure (HHP) on the production of amino acids, including GABA, in buckwheat during preservation. Buckwheat was soaked in 0–0.5 % glutamic acid solution and exposed to HHP treatment at 200 or 400 MPa. The concentrations of amino acids, except glutamic acid, increased with HHP treatment and preservation. GABA production tended to be higher in a 0.3 g/mL Glu solution under 400 MPa. The relationship between initial glutamate concentration and GABA production rate was bell-shaped, with a maximum approximately 50 µmol/g for the 200-MPa and untreated samples. The Km, Ki, and Vmax were calculated from the Michaelis–Menten equation with substrate inhibition. The Km changed after 400-MPa HHP treatment, whereas Vmax and Ki increased in a pressure-dependent manner. Combining Glu and HHP treatment can produce buckwheat with enhanced GABA production.